2010
DOI: 10.1111/j.1468-1331.2009.02917.x
|View full text |Cite
|
Sign up to set email alerts
|

EFNS guideline on the management of status epilepticus in adults

Abstract: The objective of the current article was to review the literature and discuss the degree of evidence for various treatment strategies for status epilepticus (SE) in adults. We searched MEDLINE and EMBASE for relevant literature from 1966 to January 2005 and in the current updated version all pertinent publications from January 2005 to January 2009. Furthermore, the Cochrane Central Register of Controlled Trials (CENTRAL) was sought. Recommendations are based on this literature and on our judgement of the relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
300
1
29

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 385 publications
(337 citation statements)
references
References 57 publications
7
300
1
29
Order By: Relevance
“…These doses are repeated in case of persistence or recurrence of epileptic activity. If necessary, additional phenytoin (15 18 mg/kg) or equivalent fosphenytoin is recommended [Meierkord et al 2010;Tomson et al 1986]. Alternatively, levetiracetam at 30 40 mg/kg or valproic acid at 25 45 mg/kg may be administered rapidly [Shorvon et al 2008].…”
Section: Cpsementioning
confidence: 99%
See 1 more Smart Citation
“…These doses are repeated in case of persistence or recurrence of epileptic activity. If necessary, additional phenytoin (15 18 mg/kg) or equivalent fosphenytoin is recommended [Meierkord et al 2010;Tomson et al 1986]. Alternatively, levetiracetam at 30 40 mg/kg or valproic acid at 25 45 mg/kg may be administered rapidly [Shorvon et al 2008].…”
Section: Cpsementioning
confidence: 99%
“…Consequently, current treatment options are still unsatisfactory, and mortality and morbidity rates remain high. However, in a number of areas, progress has been made including agreed upon guidelines [Meierkord et al 2010;Minicucci et al 2006] and consensus recommendations [Shorvon et al 2008;van Rijckevorsel et al 2006] on the management of the condition.…”
Section: Introductionmentioning
confidence: 99%
“…In this situation, an oral or parenteral loading dose is often administered. Patients presenting with status epilepticus refractory to benzodiazepine administration require prompt IV phenytoin administration [2,7,8]. Finally, patients with traumatic intracranial injury or symptomatic mass lesions are frequently prescribed with phenytoin for prophylaxis against seizure activity in either oral or parenteral form [9][10][11].…”
Section: Indications For Use Of Phenytoin In the Emergency Departmentmentioning
confidence: 99%
“…Mahajan et al reported a case of rapidly progressing distal limb ischemia resulting in compartment syndrome with arterial occlusion and thrombosis [31]. Finally, alternative drug regimens should be considered in situations in which efficacy has been shown to be non-inferior to phenytoin [2,10,60]. Any intravenous insertion sites should be monitored closely for pain, signs of extravasation, discoloration, or changes in perfusion and documented thoroughly [1,3].…”
Section: Preventionmentioning
confidence: 99%
See 1 more Smart Citation